Development Of Problem-Based Teaching Materials To Improve Scientific Literacy Of Fifth-Grade Elementary School Students - Sukma Laila Nur Jannah; Lia Yuliati; Widiyanti Widiyanti (UNIVERSITAS PAKUAN, 2026)
Science and Social Studies learning in elementary schools currently tends to be conventional and lacks media capable of presenting real-world problems contextually. This research aims to develop valid, practical, and effective problem-based Teaching Materials using local environmental photography to enhance the scientific literacy of fifth-grade students on ecosystem topics. Method: This study employed Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The resulting product is a printed problem-based book that integrates authentic photographs of local environmental degradation as the primary learning stimulus. Results: Expert validation results showed a high level of feasibility, with scores of 91% from material experts and 94% from media experts. The practicality test conducted by fifth-grade teachers reached a score of 96%. The effectiveness of the Teaching Materials was significantly demonstrated by the increase in students' average scores, from 68 in the pre-test to 86 in the post-test, with a normalized gain (N-Gain) score of 0.56 in the medium category. Furthermore, observation results indicated that 94% of students were actively engaged in analyzing scientific phenomena and formulating environmental solutions. Conclusion: Problem-based Teaching Materials supported by authentic photographs are proven to be valid, practical, and effective learning media solutions for improving ecosystem understanding and scientific literacy, particularly in schools with limited instructional resources.